Alternatives to Water Photooxidation for Photoelectrochemical Solar Energy Conversion and Green H2 Production. Issue 42 (22nd September 2022) - Ta, Xuan Minh Chau; Daiyan, Rahman; Nguyen, Thi Kim Anh; Amal, Rose; Tran‐Phu, Thanh; Tricoli, Antonio
Abstract: Photoelectrochemical (PEC) water splitting is considered a promising technology to produce renewable hydrogen, a clean fuel or energy carrier to replace conventional carbon‐based fossil‐fuel sources. Nevertheless, the overall solar‐to‐hydrogen efficiency and the cost‐effectiveness of this technology are still unsatisfactory for practical implementation. This can be primarily attributed to the sluggish kinetics of the anodic oxygen evolution reaction (OER) and the relatively low economic value of cogenerated O2 production. Over the past decades, there are extensive efforts to explore more kinetically favorable photooxidation reactions, which coupled with hydrogen evolution reaction (HER) can simultaneously improve H2 production yield and produce higher valuable alternatives to conventional O2 . This review aims to present recent progress on the alternative anodic choices to OER. Here, the fundamental of PEC water splitting and the critical components required for this system are first shortly summarized. Then the benefits and issues of alternative photooxidation reactions including photooxidation of water to hydrogen peroxide, chlorine, alcohol, 5‐hydroxymethylfurfural, or urea oxidation when combined with the concurrent HER, are reviewed and analyzed. This review is concluded by presenting a critical evaluation of the challenges and opportunities of these alternative HER‐coupled photooxidation reactions for solar energy production and environmental treatment. Abstract : This review article summarizes current progress on alternative reactions to photooxidation of water in a photoelectrochemical cell for solar energy conversion and green H2 . The benefits, challenges, and opportunities of the alternatives including photooxidation of water to hydrogen peroxide, of chlorine, alcohol, 5‐hydroxymethylfurfural, and urea when combined with the concurrent hydrogen evolution reaction are analyzed and discussed.